Colour class domination numbers of some classes of graphs - Venkatakrishnan, Y.; Swaminathan, V. (Algebra and Discrete Mathematics, 2014)
We compute the colour class domination number of fan graphs, double fan graphs, Helm graphs, flower graphs and sun flower graphs.